Penerapan Konseling Individu dengan Pendekatan Humanistik dalam Mengatasi Insecure pada Korban Bullying - Pratiwi, Vira; Razzaq, Abdur; Ramadoni, Muhamad Afdoli (JURNAL BIMBINGAN KONSELING FLOBAMORA, 2023)
Insecure is a condition where individuals feel insecure, unsure, afraid, anxious, and so on. This study aims to know the description of insecure victims of bullying client "G" and apply individual counseling with a humanistic approach in dealing with insecure victims of bullying client "G". This study uses a qualitative approach with a case study method. The subjects in this study were clients "G". Data collection techniques used consist of three techniques namely observation, interviews, and documentation. The data analysis included reduction of data, presentation of data, and make conclusion. The result of this study shows that the image of insecure client "G" included feels unhappy, feels insecure, doubts about ability, do something is unable, feels guilty, easily anxious, experiencing body image disturbance, withdrawing from social environment, often alone because of embarrassment, and choose not tosocialize. Application of individual counseling using the humanistic approach with client-centered technique is done 6 times meetings with a time of 45x/meeting. Implementation of this individual counseling carried out in three stages, namely, the initial stage, the core/work stage, and the final stage.